Brassinosteroids antagonize gibberellin- and salicylate-mediated root immunity in rice - De Vleesschauwer, David; Van Buyten, Evelien; Satoh, Kouji; Balidion, Johny; Mauleon, Ramil; Choi, Il-Ryong; Vera Cruz, Casiana; Kikuchi, Shoshi; Höfte, Monica (Oxford University Press, 2012)
Brassinosteroids (BRs) are a unique class of plant steroid hormones that orchestrate myriad growth and developmental processes. Although BRs have long been known to protect plants from a suite of biotic and abiotic stresses, our understanding of the underlying molecular mechanisms is still rudimentary. Aiming to further decipher the molecular logic of BR-modulated immunity, we have examined the dynamics and impact of BRs during infection of rice (Oryza sativa) with the root oomycete Pythium graminicola. Challenging the prevailing view that BRs positively regulate plant innate immunity, we show that P. graminicola exploits BRs as virulence factors and hijacks the rice BR machinery to inflict disease. Moreover, we demonstrate that this immune-suppressive effect of BRs is due, at least in part, to negative cross talk with salicylic acid (SA) and gibberellic acid (GA) pathways. BR-mediated suppression of SA defenses occurred downstream of SA biosynthesis, but upstream of the master defense regulators NONEXPRESSOR OF PATHOGENESIS-RELATED GENES1 and OsWRKY45. In contrast, BR alleviated GA-directed immune responses by interfering at multiple levels with GA metabolism, resulting in indirect stabilization of the DELLA protein and central GA repressor SLENDER RICE1 (SLR1). Collectively, these data favor a model whereby P. graminicola coopts the plant BR pathway as a decoy to antagonize effectual SA- and GA-mediated defenses. Our results highlight the importance of BRs in modulating plant immunity and uncover pathogen-mediated manipulation of plant steroid homeostasis as a core virulence strategy.